‘Responsibility to protect’ and the African Union: Assessing the AU’s capacity to respond to regional complex humanitarian and political emergencies - Freire, Maria Raquel (2016)
Despite its many institutional and political weaknesses and limitations, the African Union (AU) has been developing a variety of tools and mechanisms to respond effectively to complex disasters and emergencies (both natural and manmade) by building up a comprehensive regional security architecture. Furthermore, it has become the first and only regional or international organisation to enshrine the principle of ‘responsibility to protect’ (R2P) in its Constitutive Act. This regional approach to and formal endorsement of the R2P principle allowed it to assume a particular place in the promotion of peace and security in its area. This article aims to critically assess the effectiveness of the AU on the African continent by exploring its real capacity in preventing and responding to emergencies and violent conflicts, and therefore in rendering the principle of R2P operational. The article argues that the formalisation of principles does not necessarily mean their effective implementation. The organisation's use of the R2P principle is also greatly conditioned by internal and external factors.